2019
DOI: 10.2478/rjim-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

The role of spleen stiffness using ARFI in predicting esophageal varices in patients with Hepatitis B and C virus-related cirrhosis

Abstract: Introduction. Current guidelines recommend that all patients with cirrhosis undergo upper gastrointestinal endoscopy (UGE) screening for esophageal varices (EV). Unfortunately, UGE has a lot of disadvantages, consequently various non-invasive methods of diagnosing EV have been proposed. We evaluated if spleen stiffness (SS) measured by Acoustic Radiation Force Impulse (ARFI) is a viable technique in diagnosing EV. Methods. We recruited 178 patients with cirrhosis caused by Hepatitis B and C who underwent bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This is consistent with the findings of several previous studies. 33,34,35,36,37,38 37 Although the absolute values are lower than in this study, the general trend is similar between the two studies. The ROC curves of splenic SWV for the prediction of EVs in patients with CLD have been depicted in Figure 5 and Figure 6.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This is consistent with the findings of several previous studies. 33,34,35,36,37,38 37 Although the absolute values are lower than in this study, the general trend is similar between the two studies. The ROC curves of splenic SWV for the prediction of EVs in patients with CLD have been depicted in Figure 5 and Figure 6.…”
Section: Discussionsupporting
confidence: 62%
“…This is consistent with the findings of several previous studies. 33 , 34 , 35 , 36 , 37 , 38 Park Y et al, in their study found the mean SWVs to be 2.39 m/s ± 0.67 m/s, 2.19 m/s ± 0.73 m/s and 1.64 m/s ± 0.57 m/s, respectively, in patients with high risk, low risk and no EVs. 37 Although the absolute values are lower than in this study, the general trend is similar between the two studies.…”
Section: Discussionmentioning
confidence: 89%
“…The degree of fibrosis increases as the degree of spleen stiffness increases [18]. In a recent study by Peagu et al [29], the cut-off value for spleen stiffness measured by ARFI elastography was determined to be 2.89 m/s (sensitivity 91.4%, specificity 67.7%) in predicting esophageal varices and 3.30 m/s (sensitivity 96.4%, specificity 88.5%) for the diagnosis of large varices (> 5 mm) in the patients with hepatitis-related cirrhosis. Spleen stiffness measured by ARFI elastography is also useful in predicting outcomes (such as hepatic decompensation and death) of cirrhosis patients [30].…”
Section: Discussionmentioning
confidence: 93%
“…Their prediction algorithm for GEVs has an AUROC of 0.94 in one chronic hepatitis B validation cohort and 0.90 in the validation cohort with other CLDs [51]. SS is also a tested method for detecting EVs with an AUROC of 0.872 in Peagu R et al 's study [52]. Fierbinteanu- Braticevici C et al showed the AUROC for the detection of EVs using SS was 0.776 [53].…”
Section: The Diagnosis Of Small Varicesmentioning
confidence: 99%